Patient Preferences for Treatment in Relapsed/Refractory Acute Leukemia in the United Kingdom: A Discrete Choice Experiment - Mott DJ; Hitch J; Nier S; Pemberton-Whiteley Z; Skedgel C (Patient Preference and Adherence, 2024)
David John Mott,1 Jake Hitch,1,2 Samantha Nier,3 Zack Pemberton-Whiteley,3,4 Chris Skedgel1 1Office of Health Economics, London, UK; 2Health Economics Research Centre, Nuffield Department of Population Health, University of Oxford, Oxford, UK; 3Acute Leukemia Advocates Network, Bern, Switzerland; 4Leukemia Care, Worcester, UKCorrespondence: David John Mott, Email dmott@ohe.orgBackground: Acute leukemia is a cancer of the white blood cells which progresses rapidly and aggressively. There are two types: acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). The latter has a rare subtype: acute promyelocytic leukemia (APL). For some patients, following first-line treatment, remission is not achieved (“refractory disease”), and for others the leukemia returns after achieving remission (“relapse”). For these individuals, outcomes are typically poor. It is, therefore, important to understand patients’ treatment priorities in this context.Methods: Building upon formative qualitative research, an online survey containing a discrete choice experiment (DCE) was designed to explore patients’ treatment preferences in the relapsed/refractory setting. The DCE attributes were mode of administration; quality of life during treatment; chance of response; duration of response; and quality of life during response. Each respondent completed twelve scenarios containing two hypothetical treatments. Participants were eligible if they lived in the United Kingdom and had a diagnosis of acute leukemia. The data were analysed using a latent class model.Results: A total of 95 patients completed the survey. The latent class analysis identified two classes. For both, chance of response was the most important attribute. For class 1, every attribute was important, whereas for class 2, the only important attributes were quality of life (during treatment and response) and chance of response. A greater proportion of respondents would fall into class 1 overall, and those with ALL or APL and those more recently diagnosed were more likely to be in class 2.Conclusion: Our results indicate that patients are strongly concerned about the chance of response, as well as quality of life (to a lesser extent), when faced with different treatment options in the relapsed/refractory setting. However, there is significant preference heterogeneity within the patient population, and other treatment characteristics also matter to many.Keywords: acute leukemia, hematology, oncology, patient preferences, discrete choice experiment